POLA PENGEMBANGAN MANAJEMEN KURIKULUM DALAM MENINGKATKAN PEMBELAJARAN DI MA HIDAYATUL ARIFIN - Fathul Fauzi; Achmad Fahmi; Ashari imron (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
This study discusses the pattern of curriculum development in improving learning at MA HIDAYATUL ARIFIN. The purpose of this research is to find out the pattern of development in improving learning at MA HIDAYATUL ARIFIN. This study uses a descriptive qualitative approach. Data collection techniques used are observation, interviews and documentation. The results of the study show that the curriculum at MA HIDAYATUL ARIFIN applies two curricula for class X using the independent curriculum and class XI using the K13 curriculum, the development in entrepreneurship is taken by entrepreneurship where students are trained to make products and market the results of these products Keywords: Development, Curriculum, Improvement, Learning References Azis, Rosmiaty, ‘Implementasi Pengembangan Kurikulum’, Inspiratif Pendidikan, 7.1 (2018), 44 <https://doi.org/10.24252/ip.v7i1.4932> Bahri, Syamsul, ‘Pengembangan Kurikulum Dasar Dan Tujuannya’, Jurnal Ilmiah Islam Futura, 11.1 (2017), 15 <https://doi.org/10.22373/jiif.v11i1.61> Erica, D, H Haryanto, M Rahmawati, and I.A Vidada, ‘Peran Orang Tua Terhadap Pendidikan Anak Usia Dini Dalam Pandangan Islam. Perspektif Pendidikan Dan Keguruan, 10(2), 58- 66.’, Universal Pendidikan, april 2017, 2019, 8–22 Huda, Nurul, ‘Manajemen Pengembangan Kurikulum’, Al-Tanzim : Jurnal Manajemen Pendidikan Islam, 1.2 (2017), 52–75 <https://doi.org/10.33650/al-tanzim.v1i2.113> Nugraha, Enung, and Encep Syarifudin, ‘Peningkatan Efektivitas Pelaksanaan Program Kurikulum 2013 Di Smp Negeri Se-Kota Serang’, Visipena, 11.2 (2020), 228–42 <https://doi.org/10.46244/visipena.v11i2.1207> Qolbi, Satria Kharimul, and Tasman Hamami, ‘Impelementasi Asas-Asas Pengembangan Kurikulum Terhadap Pengembangan Kurikulum Pendidikan Agama Islam’, Edukatif : Jurnal Ilmu Pendidikan, 3.4 (2021), 1120–32 <https://doi.org/10.31004/edukatif.v3i4.511> Uliatunida, Nida, ‘Pengembangan Kurikulum Dalam Upaya Meningkatkan Pembelajaran’, Jurnal Ilmu Pendidikan Dan Dakwah, 1.2 (2019), 131–46